Ответ(ы) на вопрос:
[latex]ax^2+bx+c=a(x-x_1)(x-x_2)[/latex]
[latex]D=b^2-4ac[/latex]
[latex]x_1=\frac{-b-\sqrt{D}}{2a}[/latex]
[latex]x_2=\frac{-b+\sqrt{D}}{2a}[/latex]
---------------------
[latex]2x^2+5x-3[/latex]
[latex]a=2;b=5;c=-3[/latex]
[latex]D=5^2-4*2*(-3)=49=7^2[/latex]
[latex]x_1=\frac{-5-7}{2*2}=-3[/latex]
[latex]x_2=\frac{-5+7}{2*2}=\frac{1}{2}[/latex]
[latex]2x^2+5x-3=2(x-\frac{1}{2})(x-(-3))=(2x-1)(x+3)[/latex]
--------------
[latex]x^2-9=x^2-3^2=(x-3)(x+3)[/latex]
--------------
[latex]\frac{2x^2+5x-3}{x^2-9}=\frac{(2x-1)(x+3)}{(x-3)(x+3)}=\frac{2x-1}{x-3}[/latex]
Не нашли ответ?
Похожие вопросы